Sri Lanka’s Drug Scourge - Gunasingham, Amresh (2019)
Sri Lanka’s recent move to bring back capital punishment for convicted drug offenders has put a spotlight on growing narcotics related crime in the country. The government’s apparent tough stance is in response to concerns that Sri Lanka is re-emerging as a transit hub for global drug trafficking networks.